Review of the mixed system of constitutional control of norms in nicaragua in light of the theory of nullities - Izaba Ruiz, Carlos Ricardo (Scientific journal of social studies, 2023)
By virtue of constitutional supremacy, the constitution is the norm from which the rest of the norms in a legal system derive their validity. The constitutional control of norms is a mechanism aimed at the validity of the constitutional supremacy, by which the conformity or non-conformity of the infra-constitutional norms with respect to the constitution is reviewed, determining their invalidity if they are contrary to its provisions and principles. Invalidity is defined as legal non-existence, also expressed under the concept of nullity, from which two figures have been developed: nullity itself and voidability. The models of constitutional control of norms come to be determined by the class of invalidity that is admitted for the unconstitutional norm, because these suppose an immediate and direct applicability of the constitution (in the case of nullity) or a mediate applicability of the constitution (in the case of voidability). In the first case (annulment by operation of law), the diffuse and incidental control of the American judicial review will be held; while in the case of voidability, the Austrian, abstract and concentrated model by Kelsen will be used. The establishment of a mixed model that seeks to converge abstract and concentrated control, with the effectiveness and direct application of the constitution that results in a diffuse and incidental model, must take into account what kind of nullity is appropriate for a model whose basic premise is the direct applicability of the constitution.
Keywords: Constitutional supremacy; constitutional control; mixed control; nullity; voidability